Reposition of the Promulgation for Indonesian Legislation - Efraim Jordi Kastanya; Fitriani Ahlan Sjarif (Universitas Negeri Semarang, 2023)
Promulgation of legislation is one of the central processes of legislation making but is often forgotten by the legislators. Arrangements for the promulgation of a legislation have changed in line with the development of regulations governing the legislation making. Legislation that should not have been promulgated became promulgated and had an impact on increasing the number of legislation in Indonesia. This paper aims to place promulgation back to its proper position (reposition). The research method of this article is in the form of normative juridical research which fully uses secondary data or in the form of written legal norms. The results of the study found that legislation outside the hierarchy regulation as stipulated in Article 7 paragraph (1) of Law no. 12 of 2011 does not need to be promulgated because it is not a general binding legislation. Repositioning promulgation also requires repositioning of the understanding that the regulation outside the hierarchy of legislation cannot apply externally, namely they only apply to the Ministries/Government Institutions because the essence of promulgation is to enforce statutory regulations on the public.